Tuning micro-wrinkled graphene films for stretchable conductors of controllable electrical conductivity. (November 2018) - Feng, Chunfang; Yi, Zhifeng; Dumée, Ludovic F.; She, Fenghua; Peng, Zheng; Gao, Weimin; Kong, Lingxue
Abstract: Accurately controlling the electrical conductivity of wrinkled graphene or graphene oxide (GO) structures is challenging due to the complex sheet-to-sheet interactions and hierarchical interactions at the nanoscale. In this paper, wrinkled GO films with predictable electrical conductivity by precisely controlling thickness ranging from 0.69 to 1.68 μm were fabricated with a thermal process where a GO-coated polystyrene shrink film was isotropically shrunk. Theoretical and experimental results show consistent dependence of the wrinkle wavelength on the GO film thickness. Beyond a certain thickness threshold, poorly wrinkled structures were formed as GO sheets started delaminating from the shrink films. A coarse-grain molecule model based on molecular dynamic simulation principles was developed to understand the formation of the wrinkles, and establish a relationship between GO thickness and the wrinkle wavelength generated. The electrical resistance was found to decrease when the thickness of the GO films increases. The formed composite film can maintain a stable electrical conductivity after experiencing up to 1000 stretching-release cycles under 10% strain. With controllable electrical conductivity, the reported composites can offer potential applications as a strain sensor with tuneable sensing range and high durability. Graphical abstract: Image 1